Uarda : a Romance of Ancient Egypt $1 (BVolume 05s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"Uarda: a Romance of Ancient Egypt $1 (BVolume 05" by Georg Ebers is a historical novel written during the late 19th century, reflecting a Victorian era fascination with ancient cultures. The narrative unfolds in Ancient Egypt, focusing on the intricacies of love, power, and social dynamics amidst the backdrop of a vibrant and historically rich setting. The book closely follows the developments around Uarda, a young girl, and her interactions with the various characters that shape her life. In this volume, the storyline revolves around Nemu, a dwarf with aspirations for social mobility, who attempts to navigate the political landscape of Thebes while dealing with personal relationships. He grapples with ambitions tied to wealth and status as he aims to secure freedom and a better life through connections with the Regent and the witch Hekt. Concurrently, Uarda's journey of self-discovery and the complexities of her relationships, particularly with the leech Nebsecht and her grandparents, unfolds. The narrative intricately weaves themes of love, sacrifice, and societal constraints, creating a rich tapestry of life in ancient Egypt, as characters strive for their desires amid the rigors of their environment. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- To 332 B.C. -- Fiction; German fiction -- Translations into English